Comparative outcomes of spontaneous intestinal perforation and necrotising enterocolitis in preterm infants: a retrospective cohort study from Saudi Arabia - Kamal Ali; Abdulaziz Homedi; Mohanned Alrahili; Mohammed Almahdi; Abdulrahman Almehaid; Saif Alsaif; Lina Alsherbini; Saud Aljadaan; Omar Abbas; Norah S Alsabti; Ghiada A Almutairi; Sarah F Almujarri; et al. (BMJ Paediatrics Open)
Objective To compare risk factors, surgical management, nutritional outcomes and short-term neonatal morbidity and mortality between preterm infants diagnosed with spontaneous intestinal perforation (SIP) and necrotising enterocolitis (NEC).Design Retrospective cohort study.Setting Level III neonatal intensive care unit at a tertiary centre in Riyadh, Saudi Arabia.Patients Preterm infants born at <32 weeks’ gestation diagnosed with either SIP (n=42) or NEC (n=60) between January 2016 and December 2024.Main outcome measures Clinical characteristics, surgical intervention, nutritional outcomes, major neonatal morbidities and mortality. Multivariable logistic regression was used to identify independent predictors of mortality and prolonged parenteral nutrition (PN >60 days).Results Infants with SIP were diagnosed earlier (median 7 vs 20 days; p<0.001), had lower gestational age and birth weight and more often received postnatal hydrocortisone. Peritoneal drainage was the predominant surgical approach in SIP (98% vs 45%, p<0.001), whereas infants with NEC underwent more laparotomies (67% vs 5%) and stoma formation (42% vs 0%; both p<0.001). Infants with NEC had longer PN duration (48 vs 41 days, p=0.003), higher incidence of PN >60 days (46% vs 24%, p=0.028) and more PN-associated cholestasis (60% vs 36%, p=0.013). Growth failure at discharge was common (NEC 81%, SIP 73%). Major IVH was more frequent in SIP (41% vs 17%, p=0.007), while ROP needing therapy was more common in NEC (75% vs 52%, p=0.016). Independent predictors of mortality included sepsis (Adjusted OR (aOR) 10.5, 95% CI 2.67 to 41.22) and lower gestational age (aOR 1.35, 95% CI 1.04 to 1.77). NEC diagnosis predicted prolonged PN (aOR 0.20 for SIP vs NEC, 95% CI 0.07 to 0.58).Conclusions SIP and NEC differ significantly in timing of onset, surgical approach and nutritional trajectory. NEC is associated with greater surgical complexity and nutritional morbidity. These findings support the development of condition-specific surgical and feeding protocols.